Analysis of a familial three way translocation involving chromosomes 3q, 6q, and 15q by high resolution banding and fluorescent in situ hybridisation (FISH) shows two different unbalanced karyotypes in sibs. Issue 7 (July 1998) - Wieczorek, D; Engels, H; Viersbach, R; Henke, B; Schwanitz, G; Passarge, E
Abstract : We report on a familial three way translocation involving chromosomes 3, 6, and 15 identified by prometaphase banding and fluorescence in situ hybridisation (FISH). Two mentally retarded sibs with different phenotypic abnormalities, their phenotypically normal sister and mother, and two fetuses of the phenotypically normal sister were analysed. The terminal regions of chromosomes 3q, 6q, and 15q were involved in a reciprocal translocation, in addition to a paracentric inversion of the derivative chromosome 15. Conventional cytogenetic studies with high resolution GTG banding did not resolve this rearrangement. FISH using whole chromosome paints (WCPs) identified the chromosomal regions involved, except the aberrant region of 3q, which was undetectable with these probes. Investigation of this region with the subtelomeric FISH probe D3S1445/D3S1446 showed a balanced karyotype, 46, XX, t(3;15;6) (q29;q26.1;q26), inv der(15) (q15.1q26.1) in two adult females and one fetus. It was unbalanced in two sibs, showing two different types of unbalanced translocation resulting in partial trisomy 3q in combination with partial monosomy 6q in one patient and partial trisomy 15q with partial monosomy 6q in the other patient and one fetus. These represent apparently new chromosomal phenotypes.